Perceived discrimination, political efficacy, and political participation in American Indian adults - Wood, Zachary J.; John-Henderson, Neha A. (Frontiers in Political Science, 2024)
Psychological factors linked to political participation are largely understudied in American Indians. Prior work notes relatively low levels of participation compared to other racial and ethnic groups and suggests that identification with being AI is linked to overall levels of civic engagement in part through perceptions of group discrimination. In the current work, in a sample of a sample of 727 AI adults, we created two groups:Group 1(N = 398) reported perceived discrimination related to race, and Group 2(N=329) reported perceived discrimination not related to race or ethnicity. We investigated the relationships between individual experiences of everyday discrimination related to race, levels of political efficacy, and political participation (Group 1), and individual experiences of everyday discrimination not related to race or ethnicity, political efficacy, and political participation (Group 2). We found that greater experiences of discrimination related to race was associated with higher levels of political participation through increased levels of internal and collective efficacy. In contrast, greater experiences of race-related discrimination was associated with higher levels of political participation through lower external political efficacy. For Group 2, we found that greater experiences of discrimination not related to race or ethnicity was not directly associated with political participation, but mediation analyses revealed a relationship with lower levels of political participation through decreased internal and collective efficacy. The indirect effect through external political efficacy was not significant. Given low levels of AI political participation, political efficacy could be a target for interventions aiming to increase participation in the political system.